Lahan Sebagai Matra Dasar Ruang Lingkungan Hidup - Bambang Deliyanto (Jurnal Matematika Sains dan Teknologi, 2005)
This article discusses area as a basic component of living environment. Area can be defined by different perspectives'. The difference of perspectives and land use ethics causes conflict of interest among land user. The conflict will lead to degradation of environmental qualityl. The phenomena can be observed through factors such greenhouse effect, acid rain, ozone depletion, pollution, and social inequality.